Ergodic data rate versus the reflection amplitude factors , with N = 4, m = 1 and = 5 [dB]. - Minh Tran (7698803) (2025)
Ergodic data rate versus the reflection amplitude factors , with N = 4, m = 1 and = 5 [dB].